Primeiras noções de geometria prática (1894 -1966): a obra e as mudanças no saber profissional do professor que ensina geometria - Esquivel, Marcio Oliveira D [UNIFESP] (2019)
In 1894, it is published, in the city of Rio de Janeiro, the book Primeiras Noções de Geometria Prática” by Olavo Freire da Silva. Its publication is presented in the historical context of the establishment of the Brazilian Republican National State and the educational system in the country. At the time, Rio de Janeiro was considered the gateway for the international pedagogical modernities. In 1883, it hosts the first national Pedagogical Exhibition and among the results of this event there is the creation, in 1890, of the Pedagogium, which is a governamental organization intendend to the professional training of teachers. In addition to the Pedagogium, Pedro II College and the Court Normal School, model institutions of teaching and training, were also created in Rio de Janeiro. The professional life of professor-author Olavo Freire da Silva is directly associated with these institutions. Due to his professional life, he publishes several textbooks with remarkable editorial success, among them the book Primeiras Noções de Geometria Prática. This work was successively reissued by the year of 1960, when it arrives at its 56th edition. Its circulation through several national states and the school apropriations to which it will be submitted, makes the teaching-learning prescriptions of Freire’s book to be established as a knowledge set that is required to the performance of geometry teachers. However, the transformations occurred among the first and the last editions of the work reveal a gradual process of change in this area. Increasingly specialized knowledge is now required for the teaching of geometry. Changed by school use, Freire's book contributes to the consolidation of a new professional knowledge necessary for the performance of the teacher who teaches geometry. The developed analysis reveal that, as a complex cultural product, it contributes to the production and circulation of the book Primeiras Noções de Geometria Prática, a set of historical facts that relate to the processes of appropriation of didactic-pedagogical thoughts for the teaching of geometry in other countries, the sociability network established by the author and occupied institutional positions, to the strategic editorial games.